Cyanide-Bridged Heterobimetallic Fe(III)-Mn(II) Complex: Synthesis, Crystal Structure and Magnetic Property - Chen, Xia; Zhao, Zengdian; Wang, Ping; Zhang, Daopeng (Asian Journal of Chemistry, 2014)
A cyanide-bridged heterobimetallic trinuclear Fe(III)-Mn(II) complex with the formula {[Fe(pcq)(CN)3]2[Mn(CH3OH)4]}(1) has been synthesized with mer-[PPh4][Fe(pcq)(CN)3] (pcq = 8-(pyridine-2-carboxamido)quinoline anion) as building block and [Mn(ClO4)]2·6H2O as assemble segment. Single X-ray diffraction reveals its neutral trinuclear Fe2Mn nature, in which the two cyanide-containing building blocks acting as a monodentate ligand are coordinated to the central Mn(II) ion. Investigation over its magnetic property shows the antiferromagnetic magnetic coupling between the cyanide-bridged neighboring Fe(III) and Mn(II) ions.